Responsibility of Members of the Government in Russian and Foreign Constitutional Law. / Responsabilidad de los miembros del gobierno en el derecho constitucional ruso y extranjero. - ALBERTOVICH GAFUROV, AZAT; FEDOROVICH MALYJ, ALEKSANDR (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents a study of one of the most important institutions of constitutional law - the constitutional and legal responsibility of members of the government. The authors review Russian and foreign studies on collegial and personal constitutional legal responsibility. The conclusion made is that the constitutional and legal responsibility of members of the Government of the Russian Federation is rather voluminous, but poorly studied concept that does not have sufficient legislative regulation for the clear performance of their official duties. RESUMEN El artículo presenta un estudio de una de las instituciones más importantes del derecho constitucional: la responsabilidad constitucional y legal de los miembros del gobierno. Los autores revisan estudios rusos y extranjeros sobre la responsabilidad constitucional, legal colegiada y personal. Se llega a la conclusión de que la responsabilidad constitucional y legal de los miembros del Gobierno de la Federación de Rusia es un concepto bastante voluminoso, pero poco estudiado, que no cuenta con una regulación legislativa suficiente para el claro desempeño de sus funciones oficiales.